A CT‐based radiomics model to predict subsequent brain metastasis in patients with ALK‐rearranged non–small cell lung cancer undergoing crizotinib treatment. Issue 11 (18th April 2022) - Jiang, Yongluo; Wang, Yixing; Fu, Sha; Chen, Tao; Zhou, Yixin; Zhang, Xuanye; Chen, Chen; He, Li‐na; Du, Wei; Li, Haifeng; Lin, Zuan; Zhao, Yuanyuan; et al.
Abstract: Background: Brain metastasis (BM) comprises the most common reason for crizotinib failure in patients with anaplastic lymphoma kinase (ALK)‐rearranged non–small cell lung cancer (NSCLC). We hypothesize that its occurrence could be predicted by a computed tomography (CT)‐based radiomics model, therefore, allowing for selection of enriched patient populations for prevention therapies. Methods: A total of 75 eligible patients were enrolled from Sun Yat‐sen University Cancer Center between June 2014 and September 2019. The primary endpoint was brain metastasis‐free survival (BMFS), estimated from the initiation of crizotinib to the date of the occurrence of BM. Patients were randomly divided into two cohorts for model training ( n = 51) and validation ( n = 24), respectively. A radiomics signature was constructed based on features extracted from chest CT before crizotinib treatment. Clinical model was developed using the Cox proportional hazards model. Log‐rank test was performed to describe the difference of BMFS risk. Results: Patients with low radiomics score had significantly longer BMFS than those with higher, both in the training cohort ( p = 0.019) and validation cohort ( p = 0.048). The nomogram combining smoking history and the radiomics signature showed good performance for the estimation of BMFS, both in the training (concordance index [C‐index], 0.762; 95% confidence interval [CI], 0.663–0.861) and validation cohort (C‐index, 0.724; 95% CI, 0.601–0.847). Conclusion: We have developed a CT‐based radiomics model to predict subsequent BM in patients with non‐brain metastatic NSCLC undergoing crizotinib treatment. Selection of an enriched patient population at high BM risk will facilitate the design of clinical trials or strategies to prevent BM. Abstract : Brain metastasis is an increasing challenge in the management of ALK‐rearranged lung cancer. The CT‐based radiomics model combined smoking history and radiomics signature that is able to predict subsequent brain metastasis in patients with advanced NSCLC treated with crizotinib. Our model will allow the selection of patients at higher risk for brain metastasis and therefore, will facilitate the design of prevention trials or development of novel drugs.